The complete guide to designing and printing fabric : techniques, tutorials & inspiration for the innovative designer - Wisbrun, Laurie (A. & C. Black, 2011)
The Complete Guide to Designing and Printing Fabric is a comprehensive handbook covering everything there is to know about designing and printing fabric. The book walks readers through the entire fabric design process, from finding inspiration, through step-by-step tutorials on how to design a pattern (both digitally and by hand), looking at different printing methods (such as digital printing, screenprinting, monoprinting, stamping, stencilling, resis dying, painting and inkjet printing), to establishing and developing a fabric collection, and approaching a manufacturer. The Complete Guide to Designing and Printing Fabric is full of advice from established fabric designers with clear, easy to follow step-by-step tutorials. Textile design is a competitive industry and learning how to design fabric is something that both designers and crafters with an avid interest in fabrics are keen to learn more about. Companies such as Spoon Flower (spoon.flower.com) have emerged, offering customers an affordable way to design and print their own fabric: upload a design and they digitally print the fabric for you. This accessibility means fabric design is increasingly popular.